The Effect of Thyroid Dysfunction on Pregnancy Outcome: Systematic Review and Meta-Analysis - Sari, Heni Elmiani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Thyroid dysfunction during pregnancy certain impact on pregnancy outcomes, and neonatal growth. The incidence of pregnancy with hyperthyroidism ranges from 0.5% to 1%, leading to adverse pregnancy outcomes such as abortion, premature delivery, stillbirth, gestational hypertension, placental abruption, and premature rupture of membranes. This study aimed to analyzed the effect thyroid dysfunction on pregnancy outcomes. This was a systematic review and meta-analysis. The PICO research question as follows. Population: Pregnancy; Intervention: Dysfunction Thyroid; Comparison: Thyroid Normal; Outcome: Effect of Pregnancy. The articles were obtained from four databases: PubMed, Web of Science, Springer, and Science Direct. The Keywords were “Thyroid Dysfunction” OR “Pregnancy” OR “Outcomes” AND “Prospective Cohort” AND “Retrospective comparative”. Full text article in English with study design Cohort and retrospective comparative from 2012 to 2022, were included in this study. The steps of meta-analysis followed PRISMA flow diagram. The Articles were analyzed by the Review Manager 5.4 application A total 11 cohort and retrospective comparative from India, Israel, Denmark, Pakistan, America, Finland, and China were selected for a systematic review and meta-analysis. the data collected showed that effect of thyroid disfunction on pregnancy outcome among preterm birth by 0.87 times and was statistically significant (SMD=0.87, 95% CI=0.87 to 0.93; P<0.00001); Pre-Eclampsia by 0.70 times (SMD=0.70, 95% CI=0.50 to 0.96; P=0.03); Placenta abruption by 0.27 times (SMD=0.27, 95% CI=0.19 to 0.38; P<0.00001); Fetal Distress by 0.77 times (SMD=0,77, 95% CI=0.68 to 0.86; P<0.00001); Post-partum Hemorrhage by 0.57 times (SMD=0.57, 95% CI= 0.37 to 0.87; P<0.009).